Digital state at the leading edge - Borins, Sandford F., 1949- (University of Toronto Press, 2007)
Digital State at the Leading Edge is the first attempt to take a comprehensive view of the impact of IT upon the whole of government, including politics and campaigning, public consultation, service delivery, knowledge management, and procurement.
Keywords: Internet in public administration -- Canada.; Information technology -- Government policy -- Canada.; Internet in public administration.; Information technology -- Government policy.; Administration publique en ligne -- Canada.; Technologie de l'information -- Politique gouvernementale -- Canada.; Administration publique en ligne.; Technologie de l'information -- Politique gouvernementale.; POLITICAL SCIENCE -- Public Affairs & Administration.; POLITICAL SCIENCE -- Government -- Executive Branch.; Information technology -- Government policy; Internet in public administration; Canada; Verwaltungsautomation; E-Government; Internet; Kanada; Book